Relationship Between Physical Activity and Learning Outcomes in Physical Education for Eighth Grade Students at Junior High School 1 Japah - Zalfa Anggoro Widyastuti; Agus Raharjo (Journal of Physical Education Health and Sport, 2025)
Physical exercise is a key in physical fitness and also helps the physical education learning to succeed. However, with the digitized era and adolescents’ lifestyle changes, there has been a decrease in physical activity among students that could likely have an impact on their learning outcome in physical education. The purpose of this study is to identify the physical activity status, describe the Character Physical Education learning achievement and investigate their relationship toward physical activity among 8th grade students at Junior High School 1 Japah. This research used the quantitative correlational design. The participants included 120 eighth-grade students. Physical activity data were collected from Physical Activity Questionnaire for Adolescents (PAQ-A), and physical education learning outcome data included the administrative documentation of odd-semester report card scores. Data was analysed using descriptive and inferential statistics (normality tests, linearity tests and correlation analysis). The findings indicated that the physical activity levels of students were mostly in the 41-80th percentiles, and their learning outcomes achieved for physical education fell within the fair level for low-income populations. There was a strong significant positive relationship by correlation (r =) (0.609, p <0.05). These results highlight the need to promote physical activity of students in order to contribute positively towards learning achievement in physical education.